The Use Of Audio Visual Media In Learning To Write Advertisement Texts Class Viii Students - Siti Nurafifah; Widiastuti Widiastuti (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the use of audio-visual media in teaching students to write advertisement texts in poster form for class VIII-6 students at SMPN 87 Jakarta during the 2018/2019 academic year. Methodology: This study used a descriptive qualitative method. Data collection instruments included observation sheets, interview guidelines, assignments, and documentation. The data were analyzed using test and non-test analysis with data recap tables. The media used was a motion graphic video titled